A construção social do meia sola : trabalho, pobreza e o Programa Bolsa Família na zona da mata canavieira de Alagoas - Santos, Charles dos (Universidade Federal de São Carlos, 2017)
The research in question was conducted in the Zona da Mata Canavieira of Alagoas, Brazil, a region that is characterized by the expressive presence of sugarcane agribusiness and poverty, which is manifested in critical indicators of human and social development. The study is an analysis of the living conditions of sugarcane workers in two cities located in this territory – Branquinha and União dos Palmares – as well as of the means accessed by these men and women and their relatives to ensure family survival. The study, which is eminently qualitative, was carried out based on the bibliographical research and the accomplishment of open and semi-structured interviews with men and women of the cities mentioned above that were at the intersection of the experience as workers in sugarcane sector and the experience as beneficiaries of Bolsa Família Program. The theoretical approach that guided the research is that which deals with the precariat, this fraction of class that according to the Brazilian sociologist Ruy Braga lives squeezed between the threat of socioeconomic exclusion and the increase of the exploitation of its workforce by economic sectors; and is also, according to the British economist Guy Standing, the social segment that most suffers from the insecurity about the rights. The study showed that sugarcane workers in Branquinha and União dos Palmares oscillated between formal work and informal work, but both of which were carried out in precarious conditions. The first is related to those activities that despite be registered are extremely painful and hurtful to the physical and mental health of the worker. Some examples are sugarcane cutting, herbicide application in cane fields, and cane scrolling on slopes. The second refers to the activities done without any social protection and which are equally heavy and painful. The exploration of sand in rivers and the work in quarries are some cases. It was also seen that even the workers who were beneficiaries of a monetary transfer program such as Bolsa Família continued to accomplish precarious works and were paid well below their basic consumption needs. This leads one to believe that the program puts away the workers from the risks of complete socioeconomic exclusion, but does not give them the conditions to get rid of the need to accomplish dirty, heavy, seasonal and poorly paid jobs, such as those in the cane field. The meia sola of the title, therefore, refers to these workers, since in the region where the empirical immersion has taken place the expression has to do with precariousness, indefinition and incompleteness. The meia sola is the precarious worker of the socio-geographic space known as the Zona da Mata Canavieira of Alagoas, that is a region with huge sugar cane fields and big sugar cane mills.
Keywords: Meia sola; Trabalhadores canavieiros; Precariedade; Direitos sociais; Programa Bolsa Família; Sugar cane workers; Precariousness; Social rights; Bolsa Família Program; CIENCIAS HUMANAS::SOCIOLOGIA